1996
DOI: 10.1021/ma960405x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Conformational Characteristics of Partially Fluorinated Polyesters and Their Hydrogenated Counterparts

Abstract: From a comparative study of the polarity of poly(neopentyl glycol hexafluoroglutarate) (PNFG) and its hydrogenated counterpart, poly(neopentyl glycol glutarate) (PNG), the influence of the presence of the fluorine atoms on the conformational characteristics of polyesters is investigated. At 30°C, the experimental values of the mean-square dipole moment per repeating unit of PNG and PNFG chains, 〈µ 2 〉/x, are 5.25 and 9.16 D 2 , respectively. A critical interpretation of the experimental results using the rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…This behavior arises from differences in the modulus and orientation of the dipoles rather than from differences in the rotational populations about their respective skeletal bonds. The comparative analysis of the dipole autocorrelation coefficients of poly(neopentylglycol hexafluoroglutarate) (PNGHFG) and poly(neopentyl glycol glutarate) (PNG) confirmed these results . In this work, these studies are extended to the experimental and theoretical determination of the optical configuration parameter, Δ a , of PNGHFG networks.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…This behavior arises from differences in the modulus and orientation of the dipoles rather than from differences in the rotational populations about their respective skeletal bonds. The comparative analysis of the dipole autocorrelation coefficients of poly(neopentylglycol hexafluoroglutarate) (PNGHFG) and poly(neopentyl glycol glutarate) (PNG) confirmed these results . In this work, these studies are extended to the experimental and theoretical determination of the optical configuration parameter, Δ a , of PNGHFG networks.…”
Section: Introductionsupporting
confidence: 67%
“…The conformational energies used were taken from the analysis of the dipole moments of diethyl hexafluoroglutarate 4 and poly(neopentyl glycol hexafluoroglutarate) . Gauche states about CF 2 −C*(O*) bonds of the acid residue have an energy E σα ca.…”
Section: Theoretical Calculations and Discussionmentioning
confidence: 99%
“…The inclusion of fluorine groups into polymers, more specifically, polyesters (14), has enabled the synthesis of materials with improved chemical resistance, low water absorption, low coefficients of friction, and low surface energies. In addition, fluorinated hydroxyl‐terminated polyesters have been used as polyurethane prepolymers (5), and it has also been found that the surface properties of fluorinated polyesters make them attractive for use as biomaterials (4).…”
Section: Introductionmentioning
confidence: 99%
“…A schematic representation of the repeating units of PNGHFG and PDET in their respective all‐ trans conformations are shown in Figs 1 and 2, respectively. Skeletal bond lengths, bond angles and the conformational energies associated with the rotational states were taken from the critical analysis of the dipole moments of diethyl hexafluoroglutarate7 and poly(neopentyl glycol hexafluoroglutarate)8 and the dipole moments and temperature coefficient of the unperturbed dimensions of poly(diethylene glycol terephthalate) 9. 10…”
Section: Theoretical Calculations and Discussionmentioning
confidence: 99%
“…The following main set of statistical weights was used 7. 8 E σ α = −0.5 kcal mol −1 , E σ β = 0.7 kcal mol −1 , E σ′ = −0.6 kcal mol −1 , E ω = E ω′ = E ω″ = 1.2 kcal mol −1 . The large soluble fraction of the networks precludes the possibility of knowing the average molecular weight between crosslinking points.…”
Section: Theoretical Calculations and Discussionmentioning
confidence: 99%